Effects of Selective Serotonin Reuptake Inhibitors Exposure in Stressed Pregnant Mice on the Anxiety Behavior of the Offspring: Efek Pemberian SSRIs Prenatal pada Perilaku Kecemasan Offspring dari Model Maternal Stres - Ardianto, Chrismawan; Aprilia, Pingkan; Rahmadi, Mahardian; Sumartha, I Nengah Budi (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2024)
Background: Stress hurts problem-solving abilities, while anxiety disorders and depression are associated with unpleasant feelings and impaired daily functioning. Open field test (OFT) is used to assess anxiety-like behavior in animals by observing their exploratory behavior. Pregnant women are vulnerable to stress, which increases the risk of premature birth and low birth weight. Stress during pregnancy can also lead to preeclampsia and behavioural problems in newborns. Selective serotonin reuptake inhibitors (SSRIs), commonly used antidepressants during pregnancy, help manage mental disorders by increasing serotonin levels and regulating the endocrine system. They reduce glucocorticoid levels, thereby alleviating anxiety and stress in pregnant women. Objectives: This research investigates the correlation between the administration of SSRIs to stress-induced expectant mothers, the manifestation of depression-like behaviour, and the expression of glucocorticoid receptors in the offspring's hippocampus. Material and Methods: This study included four mouse groups: control without stress, control with offspring stress, stress model with footshock on dams and o ffspring, and stress with fluvoxamine treatment. Depressive and stress-related behaviors were measured using OFT. Results: OFT was used to assess the behaviour of offspring mice. Significant differences were observed in the number of crossings in the centre area and behaviour. The SSRI treatment showed potential anxiolytic effects, while stress led to reduced behaviour. These findings contribute to understanding anxiety-related responses and the effects of stress and SSRI treatment in animal models. Conclusions: OFT revealed significant differences in anxiety behaviour, specifically in the number of crossing centres, the centre area, and behaviour. SSRI treatment exhibited anxiolytic effects, while stress-decreased behaviour findings enhanced our understanding of anxiety responses and the impact of stress and SSRI treatment in animal models.